Principles of management - Morden, Tony 1946- (Innovative business textbooks, 2004)
A proven textbook that offers a comprehensive introduction to the theory and practice of management. In addition it now takes the reader to the leading edge of the discipline with new material on leadership, trust, stress management, teamwork, the public sector and knowledge management.